Geração de modelos digitais de superfície por meio de plataformas computacionais com estrutura vetorial e raster - Viviani, Eliane [UNESP]; Manzato, Gustavo Garcia [UNESP] (My University, 2005)
Geographic Information Systems (GIS) integrate the technologies related to Geoprocessing, with the ability to manipulate georeferenced information through data storage, management and analysis. One of the GIS applications is the generation of Digital Elevation Models (DEM) as a result of rebuilding the elevation of a region using computation tools and artificial representation. This paper presents the DEM created from a point base in two computational frameworks with different structures (vector and raster), comparing the contour lines generated from these models with the original contour lines from analog cartographic base. It was observed that one of the generated models presented some discrepancies related to real space for both GIS structures. However, using constrained Delaunay's triangulation in raster GIS a digital elevation model was generated with contour lines quite close to the original ones, with satisfactory results. A 3-D terrain representation was also created offering a very useful tool for analysis.
Generation of digital elevation models using computer frameworks with vector and raster structures
Keywords: Contour lines; DEM; Geoprocessing; GIS; Computer frameworks; Digital elevation models (DEM); Computation theory; Computer graphics; Data reduction; Information management; Mathematical models; Geographic information systems